Identity Negotiations of Colombian International Students. Issue 1 (2nd January 2018) - Velez-Gomez, Paulina; Bell, Nancy J.
ABSTRACT: Research has pointed to challenges and positive aspects of the international student experience, but it has been mainly outcome-oriented and has not addressed the ongoing identity negotiations of these students as they navigate a new cultural setting. The aim of this study was to illustrate the application of a sociocultural/dialogical framework to the analysis of identity processing by international students. Based on interviews with 14 Colombian university students in the United States, the analysis identified meanings (positionings) relative to the experience, tensions between meanings and, for some students, abstractions that served to resolve the tensions. We suggest that this dialogical framework promotes needed attention to the dynamic, ongoing nature of identity meaning creation.